SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN SANGITAN (Sambucus javanica Reinw) TERHADAP PERTUMBUHAN BAKTERI Eschericia coli DAN Salmonella thypi - Eva Sartika Dasopang (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
Leaves of sangitan (Sambucus javanica Reinw) are often found but noticed. The leaf part of the sangitan plant is used to treat swelling, insecticides, antidiarrheal, antiinfectives, wounds, smoothing the skin as it contains flavonoid chemical compounds, glycosides, anthracton glycosides, saponins, steroids / triterpenoids and tannins. Screening results of ethanol extract of sour leaves (SambucusjavanicaReinw) contain alkaloid compounds, flavonoids, glikosida, antrakinon glycosides, saponins, steroids / triterpenoids and tannins. The extraction of sangitan leaves was done by maceration using 96% ethanol. Examination of antibacterial activity of ethanol extract of sangitan leaves was done in vitro by diffusion method of wells with concentrations of 500, 400, 300, 200 and 100 mg / ml. This study used cotrimosazole as a comparator and 96% ethanol as a negative control. The extract of ethanol leaves sangitan showed anti bacterial activity against bacteria Eschericia coli and Salmonella thypi at concentration 500 mg / ml respectively 16,11 mm and 17,04 mm which is classified strong but when compared with antibiotic cotrimosazole 10 mg / ml visible diameter of inhibit ethanol extract Leaves sangitan still much lower that is 30,35 mm in bacterium Eschericia coli and 33,15 mm in Salmonella thypi bacteria whereas ethanol extract do not show inhibitory power.